The application of intraoperative molecular diagnosis in glioma surgery - HAN Zhe; LI Gang; XUE Hao (Chinese Journal of Contemporary Neurology and Neurosurgery)
Background Glioma is the most common malignant tumor of the central nervous system, and intraoperative accurate diagnosis is critical for formulating rational surgical strategies. Traditional intraoperative frozen section pathology has certain limitations, while molecular diagnosis provides a new direction for precise glioma diagnosis and treatment. This study aimed to explore the clinical value of intraoperative frozen section pathology alone and combined with molecular diagnosis to improve diagnostic accuracy and optimize surgical strategies for gliomas. Methods A total of 230 patients preoperatively diagnosed with glioma via MRI at Qilu Hospital of Shandong University from January 2021 to December 2023 were enrolled. All patients underwent intraoperative frozen section pathology (traditional diagnosis group, n = 113), while a subset also underwent molecular diagnosis (molecular diagnosis group, n = 117). Using postoperative histopathological diagnosis as the "gold standard", we evaluated the accuracy of intraoperative frozen section pathology alone and combined with molecular diagnosis, as well as the impact of molecular diagnostic techniques on surgical strategies. Results The accuracy of intraoperative frozen section pathology was 77.88% (88/113). When combined with molecular diagnosis, the accuracy of intraoperative integrated diagnosis improved to 94.87% (111/117). Among the molecular diagnosis group, 20 cases showed discrepancies between intraoperative frozen section pathology and postoperative histopathological diagnosis. Molecular diagnosis corrected 14 of these errors, resulting in only 6 cases with unresolved discrepancies, achieving a correction rate of 70% (14/20). Additionally, 86.32% (101/117) of patients had their surgical strategies optimized based on positive molecular markers, including extended tumor resection (58 cases, 57.43%) and molecular total resection (43 cases, 42.57%). Conclusions The combination of intraoperative frozen section pathology with molecular diagnosis significantly improve the accuracy of intraoperative diagnosis, optimize surgical strategies, and provide critical support for personalized treatment and precision medicine. This study also validates the clinical value of molecular diagnostic techniques in intraoperative diagnosis of glioma, laying a foundation for future advancements in diagnostic and therapeutic paradigms.